2021
DOI: 10.1371/journal.pone.0258437
|View full text |Cite
|
Sign up to set email alerts
|

Four-year safety and effectiveness data from patients with multiple sclerosis treated with fingolimod: The Spanish GILENYA registry

Abstract: Objective To describe the profile of patients with multiple sclerosis (MS) treated with fingolimod in Spain and to assess the effectiveness and safety of fingolimod after 4 years of inclusion in the Spanish Gilenya Registry. Methods An observational, retrospective/prospective, multicenter case registry, including all patients with relapsing-remitting MS (RRMS) starting treatment with fingolimod in 43 centers in Spain. Analyses were performed in the overall population and in subgroups according to prior disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…Previous observational studies on fingolimod and cardiovascular safety with follow-up durations of 2–5 years conducted in different countries have with one exception 10 not included a comparison group and reported CVD events in 0.7%–8.5% of the included patients treated with fingolimod. 7 13 This proportion of fingolimod-treated patients with CVD events during follow-up is lower than in our study where 169 of 1131 fingolimod-treated patients (14.9%) developed CVD and 141 of 1131 fingolimod-treated patients (12.5%) developed hypertension during up to 12 years of follow-up. Our results are in agreement with the LONGTERMS study, 24 a phase IIIb, open-label extension study conducted in 39 countries with up to 14 years of fingolimod exposure.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Previous observational studies on fingolimod and cardiovascular safety with follow-up durations of 2–5 years conducted in different countries have with one exception 10 not included a comparison group and reported CVD events in 0.7%–8.5% of the included patients treated with fingolimod. 7 13 This proportion of fingolimod-treated patients with CVD events during follow-up is lower than in our study where 169 of 1131 fingolimod-treated patients (14.9%) developed CVD and 141 of 1131 fingolimod-treated patients (12.5%) developed hypertension during up to 12 years of follow-up. Our results are in agreement with the LONGTERMS study, 24 a phase IIIb, open-label extension study conducted in 39 countries with up to 14 years of fingolimod exposure.…”
Section: Discussioncontrasting
confidence: 68%
“…Several observational studies with follow-up durations of 2-5 years, have shown fingolimod to have an acceptable CVD safety. [7][8][9][10][11][12][13] These observational studies did, however, not include a comparator group, and CVD safety data were collected at visits in MS clinics throughout the study observation period by each patient's treating neurologist, typically in terms of seriousness, severity, duration, and link with the DMT. [7][8][9][10][11][12][13] The aim of this study was to examine CVD safety in fingolimod-treated patients including natalizumab as reference group since natalizumab and fingolimod have similar treatment indication in MS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase 3 clinical trial on fingolimod and a study after its introduction for clinical use showed that fingolimod causes lymphopenia in 8–13% of patients ( 34 , 35 ), mostly within the 1st year of use ( 36 ). This is not surprising because fingolimod, a sphingosine-1-phosphate receptor (S1PR) modulator, works by reducing the recirculation of C-C chemokine receptor type 7+ (CCR7 + ) lymphocytes ( 37 ) and this may have relevance for protection against cryptococcal infection.…”
Section: Discussionmentioning
confidence: 99%